Exploring precision therapeutics: computational design of antisense oligonucleotides targeting AXL gene transcripts in multiple sclerosis treatment management - Shreevatsa, Bhargav; Nagaraj, Abhigna; Dharmashekar, Chandan; Jain, Anisha; Harendra, Bhavana; Siddalingegowda, Siddesh V.; Al-Mazroua, Haneen A.; Ahmad, Sheikh F.; Prasad, Shashanka K.; Srinivasa, Chandrashekar; Shivamallu, Chandan; Kollur, Shiva Prasad (Frontiers in Chemistry, 2025)
Multiple sclerosis (MS) is a chronic autoimmune illness characterized by demyelination, neurodegeneration, and inflammation in the central nervous system. The AXL gene, which codes for a receptor tyrosine kinase, has emerged as a promising therapeutic target due to its involvement in neuroinflammation and oligodendrocyte dysfunction. In the current study, we employed in silico techniques to design Antisense Oligonucleotides (ASOs) that selectively target AXL gene transcripts to modulate AXL expression and mitigate MS pathology. Three ASOs, A1, A2, and A3, were designed to specifically target the 5′ untranslated region (5′UTR) and coding region of the AXL gene transcripts. The ASOs were optimized with a focus on stability, binding affinity, and specificity towards AXL mRNA while minimizing off-target effects. To investigate ASO-mRNA interactions and gauge their ability to alter AXL expression, Molecular Docking was performed. Our analyses showed that A1, A2, and A3 had substantial interactions with AXL mRNA, with binding affinities of −9.5 kcal/mol, −10.8 kcal/mol, and −10.6 kcal/mol, respectively. The targeting of AXL gene transcripts through ASOs shows promise in reducing MS symptoms. Precision ASO-based therapies could effectively manage MS by targeting the essential pathways involved in the disease. ASOs provide a highly targeted approach for treating MS and offer a precise therapeutic strategy for this debilitating condition. The study lays the groundwork for future in vitro and in vivo studies to confirm the therapeutic potential of these ASOs for the treatment of MS.